Eu- and Tb-adsorbed Si3N4 and Ge3N4: tuning the colours with one luminescent host. Issue 50 (10th November 2022) - Braun, Cordula; Mereacre, Liuda; Chen, Zheng; Slabon, Adam; Vincent, David; Rocquefelte, Xavier; Halet, Jean-François
Abstract : The adsorption of europium and terbium at the grain boundaries of bulk β-Si3 N4 and β-Ge3 N4 and the synergic combination of both results in intriguing luminescence properties of all compounds (red, green, orange and yellow). Abstract : Phosphor-converted white light emitting diodes (pc-LEDs) are efficient light sources for applications in lighting and electronic devices. Nitrides, with their wide-ranging applicability due to their intriguing structural diversity, and their auspicious chemical and physical properties, represent an essential component in industrial and materials applications. Here, we present the successful adsorption of Eu and Tb at the grain boundaries of bulk β-Si3 N4 and β-Ge3 N4 by a successful combustion synthesis. The adsorption of europium and terbium, and the synergic combination of both, resulted in intriguing luminescence properties of all compounds (red, green, orange and yellow). In particular, the fact that one host can deliver different colours renders Eu, Tb-β-M3 N4 (M = Si, Ge) a prospective chief component for future light emitting diodes (LEDs). For the elucidation of the electronic properties and structure of β-Si3 N4 and β-Ge3 N4, Mott–Schottky (MS) measurements and density functional theory (DFT) computations were conducted for the bare and RE adsorbed samples.